Examining the Short‐, Medium‐, and Long‐Term Success of an Embodied Learning Activity in the Study of Hand Anatomy for Clinical Application. Issue 2 (17th July 2020) - Smyth, Lillian; Carter, James; Valter, Krisztina; Webb, Alexandra L.
Abstract : A student's own body provides an often disregarded site of knowledge production and corporeal wisdom. Learning via cognitive processes anchored in physical movement and body awareness, known as embodied learning, may aid students to visualize structures and understand their functions and clinical relevance. Working from an embodied learning perspective, the current article evaluates the use of an offline physical learning tool (Anatomical Glove Learning System; AGLS) for teaching hand anatomy for clinical application in medical students. Two student samples (N1  = 105; N2  = 94) used the AGLS in two different ways. In the first sample, the AGLS was compared to a traditional approach using hand bones, models and prosected specimens. Secondly, the AGLS and traditional approach were combined. The evaluation consisted of three outcomes: short‐term learning (post‐test), medium‐term applications (mock‐objective structured clinical examination, MOSCE), and longer‐term assessment (objective structured clinical examination, OSCE). Findings from the first sample indicated no significant differences between the AGLS and traditional laboratory groups on short‐ ( F (1, 78) = 0.036, P  = 0.849), medium‐ ( F (1, 50) = 0.743, P  = 0.393), or longer‐term ( F (1, 82) = 0.997, P  = 0.321) outcomes. In the second sample using the AGLS in combination with a traditional approach was associated with significantly better short‐term post‐test scores ( F (2, 174) = 5.98, P  = 0.003) than using the AGLS alone, but demonstrated no effect for long‐term OSCE scores. These results suggest an embodied learning experience alone does not appear to be advantageous to student learning, but when combined with other methods for studying anatomy there are learning gains.